Child welfare and child well-being: new perspectives from the national survey of child and adolescent well-being - Webb, Mary Bruce; Dowd, Kathryn; Harden, Brenda Jones; Landsverk, John; Testa, Mark F. (Oxford University Press, 2010)
Study design and methods / Paul P. Biemer, Kathryn Dowd, and Mary Bruce Webb -- Quality of the early caregiving environment and preschool well-being : an examination of children entering the child welfare system during infancy / Brenda Jones Harden ... [et al.] -- Risk and resilience among children referred to the child welfare system : a longitudinal investigation of child well-being in multiple domains / Anne Shaffer, Byron Egeland, and Kevin Wang -- Latent classification of physical abuse as a predictor of adolescent functioning / Charles V. Izzo ... [et al.] -- Effects of intimate-partner violence on child psychopathology / William Gardner, Kelly Kelleher, and Kathleen Pajer -- Comparative safety, stability, and continuity of children's placements in formal and informal substitute care / Mark Testa, Christina M. Bruhn, and Jesse Helton -- The social capital of youth in foster care : an assessment and policy implications / Matthew Stagner and Daniel Kuehn -- Explaining reunification and reentry 3 years after placement in out-of-home care / Richard P. Barth ... [et al.] -- Racial and ethnic diversity in the initial child welfare experience : exploring areas of convergence and divergence / Robert M. Ortega ... [et al.] -- Patterns and predictors of mental health services use by children in contact with the child welfare system / Sarah McCue Horwitz, Michael S. Hurlburt, and Jinjin Zhang -- Exits from out-of-home care and continuity of mental health service use / John Landsverk ... [et al.] -- Caregiver depression, mental health service use, and child outcomes / Barbara J. Burns ... [et al.] -- Organizational climate and service outcomes in child welfare systems / Charles Glisson -- Information management, interagency collaboration, and outcomes in child welfare agencies / E. Michael Foster, Rebecca Wells, and Yu Bai